Pengenalan Teknologi Penerbangan Drone untuk Fotografi - Widagdo, Rinosa Ari; Widodo, Dody Wahyu; Noorwahyu, Arsanto; Aviantara, Gema (Politeknik Penerbangan Indonesia Curug, 2024)
In recent years, drone technology has shown its role as a cutting-edge technology in aviation. Originally classified as a hobby, drones are now developing into an alternative solution for air transport. Activities to introduce drone technology to the public need to be carried out so that people can keep up with the development of aviation information and technology. Politeknik Penerbangan Indonesia Curug as the oldest aviation education institution in Indonesia introduced drone technology for photography to the younger generation as a concrete form of community service. This activity took place at the State Vocational High School 12 Tangerang Regency on 27 October 2023 and was attended by students from the Construction and Design Technology class. The class was chosen because of its relevance to the function of drones for photography. The introduction was carried out by explaining information about the types of drones, regulations and permits to operate drones starting from drone licences, drone pilot personnel licences, and permit procedures to the competent authorities.